Effect of supplementary feeding on the prevention of mild-to-moderate wasting in conditions of endemic malnutrition in Guatemala - Rivera Juan A.; Habicht Jean-Pierre (The World Health Organization, 2002)
OBJECTIVE: To estimate the effect of supplementary feeding on the prevention of wasting in preschool children in a rural area of Guatemala with a high prevalence of malnutrition. METHODS: Children aged 6-48 months, with a weight-for-length exceeding 90% of that of the median NCHS/WHO/CDC reference population, received either Atole, a drink with a high protein and moderate energy content, or Fresco, a drink with no protein and a low energy content. Children consuming amounts of Atole equivalent to more than 10% of the age-adjusted recommended dietary intake for energy were termed "supplemented". A comparable group of children consuming Fresco was termed "non-supplemented". The energy intake in the supplemented group was higher than that in the non-supplemented group by 16-18% of the recommended daily intake. The corresponding difference in protein intake was 45-80% of the recommended daily intake. The children were followed up at intervals of three or six months in order to evaluate their weight-for-length development. The difference between supplemented and non-supplemented children in the proportions maintaining their weight-for-length category at the end of the study intervals represented the prevention of wasting attributable to supplementary feeding (attributable prevention). Households were used as units of analysis in order to avoid cluster effects. FINDINGS: The attributable prevention in children aged 6-24 months with weight-for-length between 90% and 99.9% of the reference population at entry ranged from 0.21 to 0.26 and was statistically significant after three and six months of supplementation. However, it was not significant in children at or above 100% weight-for-length or in older children. Children above 100% weight-for-length did not become overweight as a result of supplementation. CONCLUSION: Supplementary feeding of children aged 6-24 months in populations with inadequate dietary intakes can prevent the onset of wasting in a large proportion of children.